Use of functional bandages in patients with stroke - Dreyzialle Vila Nova Mota; Lícia Vasconcelos Carvalho da Silva
Introduction Functional bandages have been used in physiotherapeutic practice with the purpose of minimizing disabilities and favoring functional improvement. However, there is still a shortage of research regarding the use of these devices in patients with neurological sequelae, especially those resulting from stroke. Objective To report the motor evolution of patients living with sequelae of stroke, who have been submitted to the use of functional bandages associated with conventional physical therapy. Materials and methods We assessed the active range of motion, strength and degree of spasticity in the flexor and extensor muscles of the wrist and elbow joints, and functionality of the upper limb during the performance of daily activities at the first and the twentieth session of conventional physical therapy associated with the use of functional bandages. Results There was an increase in range of motion and muscle strength of patients, and reduction in spasticity of the wrist and elbow flexor muscles. Conversely, the functionality scores remained similar before and after treatment. Conclusion The subjects of this study showed a good evolution in the aspects studied. Thus, the use of functional bandages associated with conventional physical therapy seems to contribute to the rehabilitation of patients with stroke sequelae. Further research needs to be conducted in order to increase the scientific evidence regarding the effectiveness of functional bandages in the treatment of patients with stroke sequelae.